Driving Torque Model and Accuracy Test of Multilink High-Speed Punch. (13th May 2018) - Li, Fuxing; Liu, Hao; Li, Menglei; Guo, Jun; Lu, Xinjian; Zhou, Jianhui; Xiao, Maohua; Wei, Weihua
Abstract : Inertia force is an important factor for operation stability and stamping precision of high-speed punch; adjusting drive torque of high-speed punch can realize effective control of inertia force. In this paper, a kind of 600 KN multilink high-speed punch inertia force balancing mechanism was designed. The calculation model of ideal inertia force was proposed based on conservation of energy and numerical analysis method. In addition, the calculation model of ideal driving torque were analyzed, simplified, and corrected by using numerical calculation and simulation methods, which solved the problem of controlling inertia force from the perspective of driving torque and realized the stability strategy planning of high-speed multilink punch press. Finally, the proposed ideal driving torque calculation model was simulated and verified by ADAMAS and bottom-dead-point accuracy test was carried out.